Research trends in esketamine for depression over the past decade: a bibliometric analysis - Zhang, Baozhou; Liu, Yifan; Zheng, Jinwei; Chen, Junping (Frontiers in Psychiatry, 2025)
BackgroundPatients suffering from depression frequently encounter extended periods of low moods and lack of enjoyment or enthusiasm for activities. It leads to suicidal thoughts and presents a potential hazard to their safety. Nowadays, there has been significant progress in researching the effectiveness and safety of esketamine in treating depression. Hence, this paper employs bibliometric analysis to investigate the evolution and future research trajectories of this domain.MethodsWe utilize Excel, VOSviewer, and CiteSpace software to generate bibliometric network visualizations to analyze, construct, and quantitatively evaluate pertinent literature, which facilitates a lucid and intuitive presentation of the trends and frontiers in this research domain.ResultsAnnual publications increased from 2015 to 2024, totaling 925 articles, with 286 studies published in 2024. The USA published the most papers (n=308), followed by China (n=260) and Canada (n=114). Three of the top journals were Journal of Affective Disorders (n=56,IF=4.90), Frontiers in Psychiatry (n=38,IF=5.44), and International Journal of Neuropsychopharmacology (n=21,IF=4.50). The most published authors were McIntyre, Roger S (n=52), followed by Hashimoto, Kenji (n=49), Rosenblat, Joshua D (n=41). The keywords that have been relevant to the topic for the last decade are “treatment-resistant depression”, “efficacy”, “antidepressant” and “suicidal ideation”.ConclusionsThis bibliometric analysis showed a significant increase in research on the use of esketamine in the treatment of depression. The main focus of current research is still the assessment of long-term use safety. In addition, the huge difference in research resources between developed countries and low- and middle-income countries remains an unresolved issue.